RECOMMENDED NOMENCLATURE OF EPIDOTE-GROUP MINERALS - Armbruster T.; Bonazzi P.; Menchetti S.; Akasaka M.; Bermanec V.; Chopin C.; Gieré R.; Soraya H.-A.; Liebscher A.; Pan Y.; Pasero M. (My University, 2006)
Epidote-group minerals are monoclinic in symmetry and have topology consistent with space group P21/m and the general ; formula A 2M3[T2O7][T04](O,F)(OH,O). Zoisite is an orthorhombic polymorph of clinozoisite Ca2Al 3[Si2O7][SiO4]O(OH) and is thus not considered a member of the epidote-group. Epidote-group minerals are divided into three subgroups. (1) Members of the clinozoisite subgroup are derived from the mineral clinozoisite Ca2Al3[Si2O 7][SiO4]O(OH) by homovalent substitutions only. The key cation-and anion-sites are Al = M2+, A2 = M2+, M1 = M 3+, M2 = M3+, M3 = M3+, O4 = O2-, O10 = (OH)-. In other words, the dominant valence as listed above must be maintained. (2) Members of the allanite subgroup are REE-rich minerals typified by the eponymous mineral "allanite". This subgroup may be derived from clinozoisite by homovalent substitutions and one coupled heterovalent substitution of the type A2(REE)3+ + M3M 2+ → A2Ca2+ + m3m3+. Thus the valences on the key sites are: Al = M2+, A2 = M 3+, Ml = M3+, M2 = M3+, M3 = M2+, O4 = O2-, O10 = (OH)-. (3) Members of the dollaseite subgroup are REE-rich minerals typified by the eponymous mineral "dollaseite". This subgroup may be derived from clinozoisite by homovalent substitutions and two coupled heterovalent substitutions of the type a2(REE)3+ + m3m2+ → A2Ca2+ + m3m3+ and M1M2+ + O4f- → mim3+ + 04O-2. Thus the valences on the key sites are: Al = M2+, A2 = M3+, Ml = M2+, M2 = M3+, M3 = M2+, O4 = F-, O10 = (OH)-. The key cation-sites M3 and Al (and, in principle, M2) determine the root name. In both clinozoisite and allanite subgroups no prefix is added to the root name if Ml = Al. The prefixes ferri, mangani, chromo, and vanado indicate dominant Fe3+, Mn3+, Cr3+, and V3+ on Ml, respectively. In the dollaseite subgroup no prefix is added to the root name if Ml = Mg. Otherwise a proper prefix must be attached; the prefixes ferro and mangano indicate dominant Fe2+ and Mn2+ at Ml, respectively. The dominant cation on A2 (other than Ca) is treated according to the Extended Levinson suffix designation. This simple nomenclature requires renaming of the following approved species: Niigataite (old) = clinozoisite-(Sr) (new), hancockite (old) = epidote-(Pb) (new), tweddillite (old) = manganipiemontite-(Sr) (new). Minor modifications are necessary for the following species: Strontiopiemontite (old) = piemon-tite-(Sr) (new), androsite-(La) (old) = manganiandrosite-(La) (new). Before a mineral name can be assigned, the proper subgroup has to be determined. The determination of a proper subgroup is made by the dominating valence at M3, Ml, and A2 expressed as M2+ and or M3+, not by a single, dominant ion (i.e., Fe2+, or Mg, or Al). In addition, the dominant valence on 04: X- or X2- must be ascertained. [M2+]A2 > 0.50, [M3+]M3 > 0.50 → clinozoisite subgroup, [M 3++ M4+]A2 > 0.50, [M2+] M3 > 0.50 → allanite subgroup, {[M2+]m3+m1-[M 3++ M4+]A2 } > 0.50 and [X-]O4 > 0.5 → dollaseite subgroup. Coupled heterovalent substitutions in epidote-group minerals require a special application of the so-called 50 % rule in solid-solution series. (1) Clinozoisite subgroup: The dominant trivalent cation on M3 determines the name, whereas the A2 cation appearing in the suffix has to be selected from among the divalent cations. (2) Allanite and dollaseite subgroups: For the sites involved in the charge compensation of a heterovalent substitution in A2 and 04 (i.e. M3 in the allanite subgroup; M3 and Ml in the dollaseite subgroup), identification of the relevant end-member formula must take into account the dominant divalent charge-compensating octahedral cation (M2+) and not the dominant cation in these sites. Formal guidelines and examples are provided in order to determine a mineral "working name" from electron-microprobe analytical data. © 2006 E. Schweizerbart'sehe Verlagsbuchhandlung.
Keywords: ALLANITE; CLINOZOISITE; DOLLASEITE; EPIDOTE-GROUP MINERALS; NOMENCLATURE